Pelaksanaan Pembelajaran Memahami Kandungan Al-Qur’an Pada Mata Pelajaran Al-Qur’an Hadis di MA Darul Ulum Palangka Raya - Ansori Sidqi; Muslimah Muslimah; Neela Afifah (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aims to describe the implementation of learning to understand the contents of the Qur'an in the Qur'an Hadith subject at MA Darul Ulum Palangka Raya, which includes preliminary, core, and closing activities, as well as identifying the main obstacles and solutions applied by teachers. This study uses a descriptive qualitative approach with field research. Data were collected through observation, structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results show that learning is carried out systematically and reflectively. In the introductory activities, teachers build students' readiness to learn through religious habits and reflective perception. In the core activities, tadabbur-based learning using lecture and question-and-answer methods encouraged students to actively construct their understanding of the meaning of Qur'anic verses and internalize the value of patience as part of the learning process. The closing activities emphasized reflection and reinforcement of Qur'anic values. The main obstacles in learning included limited media, learning time, and variations in student motivation. The solution was implemented through flexible learning strategies, strengthening teacher-student interaction, and reinforcing spiritual motivation. These findings show that Al-Qur'an Hadith learning reflects a constructivist approach that not only builds cognitive understanding but also strengthens the internalization of patience as a Qur'anic character trait.